2017
DOI: 10.1007/s40071-017-0181-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different dietary additives based on growth performance, innate immunity and disease resistance in juvenile Amur catfish, Silurus asotus

Abstract: Three different dietary additives were evaluated based on growth performance, innate immune responses and disease resistance in juvenile Amur catfish Silurus asotus. Four diets were prepared by supplementing 0.4% Song-gang Ò stone (SG), 0.05% Yucca meal (YM), 0.05% b-glucan (BG) in combination with 0.04% SG and 0.05% BG (SG ? BG) to a basal commercial diet (control; CONT). Triplicate groups of fish averaging 4.95 ± 0.05 g were fed one of the test diets between 3 and 5% body weight for 8 weeks. At the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…These increases were comparable to beneficial responses observed in response to other dietary additives, leading the authors to conclude that this mineral supplement has potential applicability as a replacement for antibiotic treatments currently in use. A similar trial of SGS dietary supplementation in juvenile Amur catfish (S. asotus) demonstrated significant growth and immune status enhancements as compared with controls, also suggesting that this mineral feed additive offers an economically appealing option for improved performance in this species (Amoah et al, 2017). Bae et al (2008) investigated the effects of dietary supplementation of SGS either alone or in combination with a "feed stimulant" in juvenile Japanese eels (Anguilla japonica).…”
Section: Effects Of Song-gang® Bio-stone In Fresh Water and Marine Fishmentioning
confidence: 99%
“…These increases were comparable to beneficial responses observed in response to other dietary additives, leading the authors to conclude that this mineral supplement has potential applicability as a replacement for antibiotic treatments currently in use. A similar trial of SGS dietary supplementation in juvenile Amur catfish (S. asotus) demonstrated significant growth and immune status enhancements as compared with controls, also suggesting that this mineral feed additive offers an economically appealing option for improved performance in this species (Amoah et al, 2017). Bae et al (2008) investigated the effects of dietary supplementation of SGS either alone or in combination with a "feed stimulant" in juvenile Japanese eels (Anguilla japonica).…”
Section: Effects Of Song-gang® Bio-stone In Fresh Water and Marine Fishmentioning
confidence: 99%
“…Other studies showed divergent effects of a Y. shidigera supplementation in different fish species. Amoah et al [10] indeed reported a beneficial impact of a 500ppm Y. schidigera meal on growth performances in juvenile Amur catfish (Silurus asotus), whilst Tidwell et al showed that the use of a supplementation with 1100ppm Y. schidigera extract in juvenile channel catfish (Ictalurus punctatus) in recirculated aquaculture system led to decrease performances and feed utilization [11].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that dietary QS extract can enhance the growth of common carp (Francis et al, 2002;Serrano, 2013;Serrano et al, 2000) and Nile tilapia (Elkaradawy et al, 2021;Francis et al, 2001). On the other hand, previous studies have demonstrated that YS can enhance the growth of catfish (Amoah et al, 2017;Güroy et al, 2014;Kelly & Kohler, 2003), carp (Dawood et al, 2021;Wang et al, 2020), Atlantic salmon (Gu et al, 2015), European seabass (Elkhayat et al, 2019), Pacific white shrimp (Yang et al, 2015) and Nile tilapia (Elbialy et al, 2020;Gaber, 2006;Njagi et al, 2017). In contrast, YS's dietary supplementation did not improve the FCR or growth of channel catfish (Tidwell et al, 1992).…”
Section: Ta B L Ementioning
confidence: 92%